COMPARATIVE ANALYSIS OF POSTURAL STATE NON-ATHLETEST AND JUDO ATLETES OF YOUNG ADOLESCENTS - Radojica Dačević; Veselin Jovović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The problem of this work is to determine the situation and possible differences in postural state between judo athletes and non-athletes of younger adolescent age. Research is conducted on a sample of 186 examinees of 12 and 13 years old, from the territory of Podgorica and Niksic. The total sample is divided into two subsamples as follows: non-athletes subsample (96) from the 4th grade of elementary school and subsample of judo athletes (90) from the 14 judo clubs. Postural state is assessed by using the method of Napoleon Wolanski. H square test (χ2) ie. Yet׳s correction for continuity in tables 2x2 was applied in determining possible differences of frequency of postural disorders between non-athletes and judo athletes of younger adolescent age. It has been determined that there is a statistically significant difference in the prevalence of postural disorders in holding abdomen between sub samples of judo athletes and non-athletes. It was indicated that the prevalence of this disorder is in higher percentage at judo athletes. In other segments of the body were not determined any statistically significant differences between judo athletes and non-athletes of the same age.